2016
DOI: 10.1016/j.canlet.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin enhancement of the radiosensitivity of human breast cancer cells is associated with the modulation of proteins involved in estrogen biosynthesis

Abstract: Enhancing the radiosensitivity of cancer cells is one of the most important tasks in clinical radiobiology. Endocrine therapy and radiotherapy are two cancer treatment modalities which are often given together in patients with locally-advanced breast cancer and positive hormone-receptor status. Oncostatic actions of melatonin are relevant on estrogen-dependent mammary tumors. In the present study, we wanted to evaluate the effects of the combination of ionizing radiation and melatonin on proteins involved in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 40 publications
3
64
0
Order By: Relevance
“…In this case, the animals were treated with melatonin in advance of the radiation therapy. The second study yielded similar results and suggested that the enhancing action of melatonin in radiation-treated cancers related to its modulation of p53 [223]. …”
Section: Melatonin and Cancer Progressionmentioning
confidence: 83%
“…In this case, the animals were treated with melatonin in advance of the radiation therapy. The second study yielded similar results and suggested that the enhancing action of melatonin in radiation-treated cancers related to its modulation of p53 [223]. …”
Section: Melatonin and Cancer Progressionmentioning
confidence: 83%
“…Pretreatment with melatonin on MCF-7 breast cancer cells 1 week before radiation could sensitize cancer cells to the ionizing effects of radiation, through inhibiting proliferation, promoting cell cycle arrest and inhibiting proteins involved in double-strand DNA break repair [79]. Another study suggested the enhancing effect of melatonin on the radiosensitivity of human breast cancer cells might be associated with the increase of p53 expression [80]. …”
Section: Experimental Studiesmentioning
confidence: 99%
“…Alonso-Gonzalez et al pointed out that the pretreatment of 1 nM melatonin before radiation could elevate the sensitivity of human breast cancer cells to radiotherapy by reducing the active estrogens levels in cancer cells through the increased p53 expression [243]. It was also found that melatonin-based creams could significantly lower the occurrence of acute radiation dermatitis in a double-blind randomized trial [244].…”
Section: Bioactivities Of Melatoninmentioning
confidence: 99%